Study the rate of changes in some chemical and microbiological properties of concentrated and diluted orange juice samples during storage at different temperatures - Altaher O. Alzwei , Najah O. Elfeturi (Journal of Pure & Applied Sciences, 2019)
Three different concentrations of juice (15%, 30% and 65%) were used,  as well as  two samples of sterile juice at 30% and 65% concentration, respectively, with pure strains of yeasts and molds (Sacchromyces cerevisiae and Penicillium notatum). The results of the chemical tests revealed slight changes in the values of the tests with differences in these values between the months in the juice samples at a concentration of (65%). For the concentration (15, 30%), the results showed a high percentage of acidity (0.4-0.3%) with a decrease in the percentage of concentration by (2-5%). Microbiological tests indicated an increase in the total number of microbes for juice samples at a concentration of 15,30% (4.5 x 102, 9.6 × 103C.F.u/ ml), (2.0 x 10, 7.0 × 104 C.F.u/ ml)  respectively, while the total microbial number of juice samples decreased by 15% at the end of the third months of storage (7.0 x104  and 8.0 × 103 C.F.u/ ml). The results did not indicate.  The presence of coliform bacteria in any of the studied samples. This is a good indicator of adherence to the requirements of good health practices and the high microbiological quality of water used in manufacturing processes. The results of the isolating during the storage period at all the concentrations showed that there were 3 species of bacterial species that follow the species: Bacillus, Micrococcus and Lactobacillus. As for yeast and mold, the results showed that most of the isolates included Pencillium, as well as species of yeast: Sacharomyces, Rhodotorula and Torulopsis. On the other hand, the results of sterile and inoculated samples by Sacchromyces cerevisiae and Penicillium notatum (30% and 65%) showed a significant increase in the microbial number at concentration (30%) during the months of storage, while the was no microbial growth at the concentration of 65%. The concentrated orange juice (65%) did not dilute with relatively high chemical and microbiological quality for 3 months at 4 °C compared to diluted juice samples. The rate of chemical and microbiological changes was directly proportional to the high dilution and storage temperature.